Effects of granular collisions on the rapid coarse-grained materials flow. Issue 4 (30th April 2019) - Federico, F.; Cesali, C.
Abstract : A continuum model to predict the mobility of landslides is developed according to the formulation by Savage and Hutter as well as the main 'microscopic aspects' affecting the rapid sliding of granular masses. Conservation of mass and momentum equations, describing the geometry and velocity evolution during the motion, are re-written by considering the effects of collisions between solid grains ('granular temperature' and 'dispersive pressures') typically occurring within a basal thin 'shear' layer, causing a 'fluidification' effect and corresponding energy dissipations. To this purpose, a 'frictional−collisional' rheological law allowing to simulate the energy dissipation related to grain inelastic collisions and friction, simultaneously acting within the basal 'shear layer', is developed and applied . The interstitial pressures, and their possible increment along curved paths related to centrifugal force, and the mass variation due to erosion/deposition processes are also considered. The numerical simulation of a documented experimental test is finally carried out.